Manual de implementación de un proceso hardening para mitigar vulnerabilidades en el servidor web nginx de la Unach - Pinduisaca Guashpa, Karina Paola (2022)
Today, computer security has become a critical point in organizations because most of the work and academic processes are supported by computer infrastructures, under communication networks and the Internet, which are highly exposed to information security risks. Therefore, in this research project, a manual for the implementation of a hardening process was prepared to mitigate vulnerabilities in the UNACH Nginx web server, thus protecting the security of the information. The investigation is inferential due to the pre and post-analysis of the vulnerabilities; an analysis of the current situation of the server was carried out, finding a total of 7 header vulnerabilities. Finally, using Pentest Tools, the scan of open ports was performed: 80 and closed ports: 113 and 443; In addition, the CPU usage from 1.8 was reduced to 0.078%, as well as the server response time improved from 5.2 to 1.09 seconds, thus confirming the effectiveness of the implementation of the hardening process.